Investigation of salt-tolerant rhizosphere bacteria from seawater-intruding paddy rice field in Vietnam - Cuong, Ho Tu; Cuong, Bui Van; Thuong, Lam Thuong; Hoang, Tran Mai; Huong, Luong Thi Thu; Phuong, Pham Thi Diem; Son, Nguyen Giang; Canh, Nguyen Xuan (Academia Journal of Biology, 2020)
Salt‐tolerant plant growth‐promoting rhizobacteria (ST‐PGPR) are known as potential tools to improve rice salinity tolerance. In this study, we aimed to investigate the plant growth‐promoting rhizobacteria community richness of the paddy rice fields in Soc Trang and Ben Tre Provinces where were seriously affected by sea level rise. The salinity in the sampling sites ranged from 0.14‰ to 2.17‰ in November 2018, the rainy season. The microbial abundance of samples was evaluated by spreading the samples in tryptic soy agar (TSA) medium supplemented with various concentrations of NaCl. With the increase of salt concentration up to 10% NaCl, a total number of bacteria decreased for all the samples, ranging from 106 to 104 CFU/g, and bacterial colonies were not observed at 30% NaCl. Among a total of 48 salt-resisting bacteria isolated from the rice paddy field mud surrounding the rice root, 22 isolates were able to produce indole-3-acetic acid (IAA: phytohormone for the plant growth). Seventeen out of 48 isolates were able to grow in the medium without nitrogen or phosphor sources. Six isolates having high IAA producing activity, nitrogen fixation and phosphate solubilization were belonged to Bacillus (DT6, LT16, and LHT8), Halobacillus (DT8), Aeromonas (LHT1), and Klebsiella (LHT7) genera. All the sequences of the strains DT6, DT8, LT16, LHT1, LHT7, and LHT8 were registered in the GeneBank with the accession numbers MK335670, MK335671, MK335672, MK335673, MK335674, and MK335675, respectively.